Video Introduction to Issue 11 - Gilles Bertheau (Angles)
This issue of Angles investigates the diverse aspects of the notion of game, gaming, gambling in the Anglophone world, today and in the past. The perspectives range from theoretical writing, literature, cinema, civilization, pedagogy to video games, in England and the United States.